A Central Park of their Own: Public Parks and the New South Movement, 1865-1920 - Gallo, Steve (2021)
The end of the Civil War, the demise of the Confederacy, and the abolition of slavery brought economic, political, and social tumult to the South. Cities and railroads lay in ruins, millions of dollars of southern capital (much of it in the form of human chattel) was lost, conservative governments were replaced with Republican administrations, and black southerners overturned the antebellum racial hierarchy with their assertions of civil and political rights. In response, a group of white southerners called for the creation of a New South, one characterized by a return of stability and prosperity. The path toward this future lay, they insisted, in accepting the reality of abolition and emulating the industrial economies previously established in the North. Consequently, they sought to grow and modernize southern cities along the lines of their northern counterparts between 1865 and 1920. This process of urbanization would, New South boosters believed, allow the region to regain, and eventually surpass, its antebellum status while simultaneously reintegrating it into the nation. But a key question remained: how does one convince a (white) southern populace, still reeling from the shock of military defeat and highly skeptical of practices associated with the conquering North, that an embrace of a New South did not require forsaking all that they had known? “A Central Park of their Own: Public Parks and the New South Movement, 1865-1920” presents one answer to the above question. As the first historical study dedicated to the convergence of the New South movement and the nineteenth-century urban parks movement, the thesis reveals that public space played a central role in both modernizing the built environments of southern cities and familiarizing southerners with, and conforming them to, the expectations of life in a modern, industrial society. Using new archival material from the Virginia Museum of History & Culture, the Atlanta History Center, the Filson Historical Society, and the Historic New Orleans Collection, in conjunction with contemporary published sources, we can see how public parks were used to both project the appearance of material progress to outsiders and conform local populations to prescribed behavioral standards. This thesis blends administrative records, design plans, promotional material, newspaper accounts, and personal reminiscences to compare the intended social effects of southern parks with the realities of public usage. The result reveals public parks as a crucial means of easing southerners’ transition into modernity. Each chapter focuses on a different southern city that serves as a case study: Richmond, Virginia; Atlanta, Georgia; New Orleans, Louisiana; and Louisville, Kentucky. By examining park-building initiatives that took place in these varying contexts we can observe the common ambition shared by city leaders across the postbellum South as well as the unique challenges to modernization created by individual circumstances. What becomes clear is that there was not one New South but many, each shaped by its distinct economic, social, political, and geographical conditions. This thesis embraces this diversity in order to develop a nuanced interpretation of the New South movement. Using public parks as a critical lens, it examines the range of experiences possible across the post-war urban South and asks: how did New South leaders attempt to balance their desire for conformity with the social demands of their respective populations?